Unambiguous detection of nitrated explosive vapours by fluorescence quenching of dendrimer films - Paul Meredith (Nature Communications, 2015)
Unambiguous and selective standoff (non-contact) infield detection of nitro-containingexplosives and taggants is an important goal but difficult to achieve with standard analyticaltechniques. Oxidative fluorescence quenching is emerging as a high sensitivity method fordetecting such materials but is prone to false positives—everyday items such as perfumeselicit similar responses. Here we report thin films of light-emitting dendrimers that detectvapours of explosives and taggants selectively—fluorescence quenching is not observed for arange of common interferents. Using a combination of neutron reflectometry, quartz crystalmicrobalance and photophysical measurements we show that the origin of the selectivity isprimarily electronic and not the diffusion kinetics of the analyte or its distribution in the film.The results are a major advance in the development of sensing materials for the standoffdetection of nitro-based explosive vapours, and deliver significant insights into the physicalprocesses that govern the sensing efficacy.